Stillbirths: progress and unfinished business. Issue 10018 (6th February 2016) - Frøen, J Frederik; Friberg, Ingrid K; Lawn, Joy E; Bhutta, Zulfiqar A; Pattinson, Robert C; Allanson, Emma R; Flenady, Vicki; McClure, Elizabeth M; Franco, Lynne; Goldenberg, Robert L; Kinney, Mary V; Leisher, Susannah Hopkins; et al.
Summary: This first paper of the Lancet Series on ending preventable stillbirths reviews progress in essential areas, identified in the 2011 call to action for stillbirth prevention, to inform the integrated post-2015 agenda for maternal and newborn health. Worldwide attention to babies who die in stillbirth is rapidly increasing, from integration within the new Global Strategy for Women's, Children's and Adolescents' Health, to country policies inspired by the Every Newborn Action Plan. Supportive new guidance and metrics including stillbirth as a core health indicator and measure of quality of care are emerging. Prenatal health is a crucial biological foundation to life-long health. A key priority is to integrate action for prenatal health within the continuum of care for maternal and newborn health. Still, specific actions for stillbirths are needed for advocacy, policy formulation, monitoring, and research, including improvement in the dearth of data for effective coverage of proven interventions for prenatal survival. Strong leadership is needed worldwide and in countries. Institutions with a mandate to lead global efforts for mothers and their babies must assert their leadership to reduce stillbirths by promoting healthy and safe pregnancies.